Seismicity characteristics based on the spatiotemporal ETAS model in North China from the perspective of different cut-off magnitude - Jinmeng Bi; Fuyang Cao; Yong Ma (PLoS ONE, 2025)
To explore the effect of the cut-off magnitude on the declustering of earthquake sequences, the calculation of seismicity parameters, the earthquake occurrence rate, and the hazard level of North China at present, we employed a stochastic declustering method based on the spatio-temporal ETAS model to decluster under different the cut-off magnitudes. And we have undertaken comprehensive research on the declustered distribution characteristics, seismicity parameters, and earthquake occurrence rates. The research results show that the selections of the cut-off magnitudes can lead to certain differences in the declustering results. As the cut-off magnitude increases, the declustering rate shows a certain downward trend, and the Poisson characteristics become more prominent. The stochastic declustering method does not significantly change the spatio-temporal statistical characteristics of seismicity parameters. Combining the analysis of the spatial distribution of the background earthquake occurrence rate, low b-value, and clustering rate in North China under different cut-off magnitudes, we found that regions including the intersection area of the Zhangjiakou-Bohai seismic belt and the Tanlu seismic belt, and the western part of the northern margin of the Ordos have relatively high seismic hazard. Some seismic belts, including the Zhangjiakou-Bohai seismic belt, exhibit a correlation among relatively high background seismicity, high crustal strain rate, and strong earthquakes. We can provide basic sequence data and technical support for the judgment of the dangerous state of moderate and strong earthquakes. This will further enhance our understanding of the laws of seismic activities in North China.